The Expanding 3 kpc Arms Are Neither Expanding nor Spiral Arms but X1 Orbits Driven by the Galactic Bar - Jayender Kumar; Mark J. Reid; T. M. Dame; Simon P. Ellingsen; Lucas J. Hyland; Andreas Brunthaler; Karl M. Menten; Xing-Wu Zheng; Alberto Sanna (The Astrophysical Journal)
Near the center of our Milky Way is a bar-like structure and the so-called Expanding 3 kpc arms. We currently have limited knowledge of this important region, since we are about 8.2 kpc from the center and cannot directly observe it at optical wavelengths, owing to strong extinction from interstellar dust. Here we present extremely precise very long baseline interferometry measurements of H _2 O maser sources from the BeSSeL Survey, where extinction is not a problem, which accurately determine the three-dimensional locations and motions of three massive young stars. Combined with previous measurements, these stars delineate a trail of orbits outlining the Milky Way’s Galactic bar. We present the first measurements capturing the dynamics of quasi-elliptical (X1) orbits around the Galactic bar. Our findings provide evidence substantiating the existence of such orbits populated by massive young stars. Our measurements of the position and velocity of a number of massive young stars, previously identified with the Expanding 3 kpc arms, show that they are more likely located in the X1 orbits about the Galactic bar. Also, some stars previously assigned to the Norma spiral arm appear to be in these orbits, which suggests that this spiral arm does not extend past the end of the bar.